2004
DOI: 10.1139/g04-031
|View full text |Cite
|
Sign up to set email alerts
|

Colocation between a gene encoding the bZip factor SPA and an eQTL for a high-molecular-weight glutenin subunit in wheat (Triticum aestivum)

Abstract: The quality of wheat grain is largely determined by the quantity and composition of storage proteins (prolamins) and depends on mechanisms underlying the regulation of expression of prolamin genes. The endosperm-specific wheat basic region leucine zipper (bZIP) factor storage protein activator (SPA) is a positive regulator that binds to the promoter of a prolamin gene. The aim of this study was to map SPA (the gene encoding bZIP factor SPA) and genomic regions associated with quantitative variations of storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…QTL have traditionally been statistically analyzed by comparison between the genotypes of marker genes and the occurrence of the trait among naturally occurring genetic variants [5,11,27,59]. Recently, transcripotmic information has been used for QTL, which is referred to as expression QTL (eQTL), thereby clarifying the genes directly related to metabolism, such as those coding for enzymes and transporters, and the regulator genes such as the transcription factors [16,40,53,55,56,86]. In addition to transcriptomic data, metabolomic data may be capable of application to QTL analysis.…”
Section: Future Prospectsmentioning
confidence: 99%
“…QTL have traditionally been statistically analyzed by comparison between the genotypes of marker genes and the occurrence of the trait among naturally occurring genetic variants [5,11,27,59]. Recently, transcripotmic information has been used for QTL, which is referred to as expression QTL (eQTL), thereby clarifying the genes directly related to metabolism, such as those coding for enzymes and transporters, and the regulator genes such as the transcription factors [16,40,53,55,56,86]. In addition to transcriptomic data, metabolomic data may be capable of application to QTL analysis.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Genes controlling expression may be identified in a mapping study that isolates regions of these chromosome arms conferring variation for glutenin protein. Previous investigations have identified the chromosomal location of storage protein regulators (Guillaumie et al 2004;Prasad et al 1999;Colas des Frances and Thiellement 1985). Guillaumie et al (2004) mapped SPA to chromosome group 1L, the same chromosomal arm as the HMW glutenin structural genes.…”
Section: Agp-lmentioning
confidence: 99%
“…Previous investigations have identified the chromosomal location of storage protein regulators (Guillaumie et al 2004;Prasad et al 1999;Colas des Frances and Thiellement 1985). Guillaumie et al (2004) mapped SPA to chromosome group 1L, the same chromosomal arm as the HMW glutenin structural genes. Perretant et al (2000) mapped bread-making quality and identified QTLs for dough strength on chromosomes 5D, 1A and 3B.…”
Section: Agp-lmentioning
confidence: 99%
See 2 more Smart Citations